Pendekatan Probabilistik Berbasis PERT dengan Visualisasi TFN pada Penjadwalan Proyek Konstruksi - Ismatul Khasanah; Lila Ayu Ratna Winanda; Munasih Munasih; Annur Ma'ruf (Jurnal Talenta Sipil, 2026)
Uncertainty regarding the duration of activities is a major factor affecting the reliability of construction project schedules. Variability in resources, field conditions, material supplies, and other technical conditions often cause deviations between planned and actual durations. Therefore, this study aims to analyze project duration using the Program Evaluation and Review Technique (PERT) based on three-point estimates, namely optimistic (a), most likely (m), and pessimistic (b), and to visualize the duration range through Triangular Fuzzy Number representation to clarify the variation in estimates for each activity. The methods used in this study include collecting duration estimates (a, m, b) through structured interviews, calculating the Expected Time (te) for each activity, and compiling a work network using the Precedence Diagram Method (PDM) with Microsoft Project to determine the critical path and total project duration. The results of the study show that the total project duration is 170 days, with several activities on the critical path determining the project completion time, while probabilistic analysis results in a 70% chance of project completion within the target duration. The uncertainty of scheduling analysis can be resolved with a triangular fuzzy number visualization approach to extend the optimistic, most likely, and pessimistic time limits for each activity. Based on these results, this study is expected to encourage the application of PERT analysis based on three-point estimates visualized in the form of triangular distributions for each activity as a basis for setting target durations and making more realistic project acceleration decisions.